2018
DOI: 10.4049/jimmunol.1701282
|View full text |Cite
|
Sign up to set email alerts
|

Hu Antigen R Regulates Antiviral Innate Immune Responses through the Stabilization of mRNA for Polo-like Kinase 2

Abstract: Retinoic acid-inducible gene I (RIG-I)-like receptors (RLRs), RIG-I, and melanoma differentiation-associated gene 5 (MDA5) play a critical role in inducing antiviral innate immune responses by activating IFN regulatory factor 3 (IRF3) and NF-κB, which regulates the transcription of type I IFN and inflammatory cytokines. Antiviral innate immune responses are also regulated by posttranscriptional and translational mechanisms. In this study, we identified an RNA-binding protein HuR as a regulator for RLR signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Therefore, in this study, we investigated the contribution of HuR to the posttranscriptional regulation of genes involved in the innate immune system. In a previous study, we showed that HuR regulates the innate antiviral immune response by stabilizing the mRNA of polo-like kinase 2 (PLK2), which facilitates nuclear translocation of IRF3 induced by RLRs 20 . Here, we provide evidence suggesting that HuR is involved in the TLR3-mediated antiviral innate immune response by stabilizing the mRNA of Atp6v0d2 , which encodes a subunit of vacuolar-type H + adenosine triphosphatase (V-ATPase) required for the acidification of intracellular vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this study, we investigated the contribution of HuR to the posttranscriptional regulation of genes involved in the innate immune system. In a previous study, we showed that HuR regulates the innate antiviral immune response by stabilizing the mRNA of polo-like kinase 2 (PLK2), which facilitates nuclear translocation of IRF3 induced by RLRs 20 . Here, we provide evidence suggesting that HuR is involved in the TLR3-mediated antiviral innate immune response by stabilizing the mRNA of Atp6v0d2 , which encodes a subunit of vacuolar-type H + adenosine triphosphatase (V-ATPase) required for the acidification of intracellular vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to TTP and other ARE-biding proteins, ELAVL1 is an ARE-binding protein that stabilizes mRNAs. This protein predominantly localizes in the nucleus but translocates into the cytoplasm in response to viral infection, hypoxic stress, and DNA damage [102][103][104]. Subsequently, ELAVL1 competes against other ARE-binding proteins for ARE sites and therefore enhances the stability and translation of target mRNA.…”
Section: Posttranscriptional Mechanisms Regulating Host Inflammatory mentioning
confidence: 99%
“…HuR is also involved in viral responses through the activation of RLR. HuR promotes IRF3 nuclear translocation via the increased stability of Plk2 mRNA [104]. In contrast, mice specifically lacking ELAVL1 in macrophages show exacerbated inflammatory responses in chemically induced colitis [135].…”
Section: The Role Of Posttranscriptional Regulation In Immune Homeostmentioning
confidence: 99%
“…RT-PCR was performed with the following primers: Mtm1, sense 5Ј-ATCTTAGGAG-GATCGCAACG-3Ј, reverse 5Ј-TACCGACAAGAGGCTGA-CTG-3Ј; Mtmr1, sense 5Ј-TCCATTTATGGGAGCAGTGA-3Ј, reverse 5Ј-TGCACCAATCTTCTCCACTC-3Ј; Mtmr2, sense 5Ј-AGCAGAAATGGAGGAACCAG-3Ј, reverse 5Ј-CGCTCCATGCTCTTGAAATA-3Ј; Mtmr3, sense 5Ј-TGGG-AATGTATTCTGCTCCA-3Ј, reverse 5Ј-CAATGCTG-GAGCTTGTAGGA-3Ј; Mtmr4, sense 5Ј-TGTGTCCT-GGAAATGAAGA-3Ј, reverse 5Ј-AAACTGTTCAGGTGGC-TTCC-3Ј; Mtmr6, sense 5Ј-TTCCGGTCCTATCCTACTGC-3Ј, reverse 5Ј-TGAAGCAAATGCTCATCCTC-3Ј; Mtmr7, sense 5Ј-CCAGTTTGGGAACTTCCTGT-3Ј, reverse 5Ј-GGCAGCTCGATTCTTCCACA-3Ј; Mtmr8 sense 5Ј-GGCT-CTCTGGGTACCATCAT-3Ј, reverse 5Ј-GAGTGGACAAT-GCCTCAATG-3Ј. Primer for Ifnb, Il6, Il10, Cxcl10, and 18s were described previously (33,34).…”
Section: Rna Isolation and Rt-pcrmentioning
confidence: 99%
“…Other plasmids were described previously (33). After 24-h transfection, luciferase activity was measured as described previously (33,34).…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%